Ad Hominem Fallacy in the Second US Presidential Debate 2020: Donald Trump, the King of Ad Hominem - Shofi, Afdila Puspita Syifa'atus; Widyastuti, Widyastuti (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2022)
The purpose of this study is to reveal and to identify the sorts of Ad Hominem fallacies used by one of the presidential candidates, Donald J. Trump, during the second US presidential debate in 2020 because Trump is named as the king of ad hominem. This study applied Damer, (2009) classification theory of ad hominem fallacy, which includes three categories; Abusive, poisoning the well and two-wrongs fallacy was used in this study. The descriptive qualitative approach is used in this study by collecting, arranging, analyzing and summarizing the data. Only two of the three kinds of ad hominem fallacy were found in this study. Based on the finding, it can be concluded that the Abusive Ad Hominem fallacy became the most often appearing category used by Trump using the pronoun you and he to attack directly to his opponent. Donald J. Trump's second dominant type is poisoning the well using the future tense modal will and wouldn’t.